Meningkatkan Kualitas Waktu Pelayanan Administrasi Kantor Desa dengan Pemanfaatan Microsoft Access Berjaringan LAN (Local Area Network) - Agung Winarno; Meisa Isnaini (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
The application product for village office administration services using Microsoft Access with LAN networks is the result of research related to the need of excellent service for correspondences at the village office. Product development has ten stages, which are the analysis of potential and problems, data collection, product design, design validation, design revisions, product trials, product revisions, product trials after revision, product revisions, and final production. The results of the product validation indicate that this application is feasible to use. The results of the use of the product indicate that the majority of respondents (village officials) stated that the application system of Microsoft Access-based village administration using LAN networks is very helpful in improving the quality of correspondence services in village offices, especially related to the writing of an inbox agenda book, an outgoing agenda book, letter making. and disposition.Keywords: service applications; service quality; village administration.